Pathways to sustainable travel: Examining the causal influence of low-carbon tourism, experience, and satisfaction on revisit intentions - Janchai, Napaporn; Suvittawat, Adisak (Edelweiss Applied Science and Technology, 2025)
The tourism industry is a significant contributor to global carbon emissions. Consequently, low-carbon tourism (LCT) plays a crucial role in mitigating environmental impacts while enhancing the competitiveness of tourism destinations. This study aims to examine the causal relationships among low-carbon tourism, tourist experience, tourist satisfaction, and revisit intentions, thereby addressing a notable gap in sustainable tourism research. Using structural equation modeling (SEM), data were collected through questionnaires from 510 Thai tourists who participated in LCT activities at Khao Yai National Park, a prominent nature-based tourism destination in Thailand. The findings reveal that low-carbon tourism significantly enhances tourists’ experiences, which in turn positively influence their satisfaction and intention to revisit LCT destinations. Furthermore, tourist experience and satisfaction were found to mediate the relationship between low-carbon tourism and revisit intention. Among the variables, low-carbon tourism exerted the strongest direct influence on revisit intention, followed by tourist experience and satisfaction, respectively. This study advances sustainable travel behavior theory and offers practical recommendations for policymakers and destination managers. It emphasizes integrating low-carbon principles across tourism sectors—activities, transport, accommodation, local product consumption, and waste management—to enhance tourist experiences and promote environmental and tourism sustainability.